2014
DOI: 10.1016/j.brainres.2014.05.034
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of the right hemisphere in reading comprehension: A DTI study

Abstract: The Simple View of reading emphasizes the critical role of two factors in normal reading skills: word recognition and reading comprehension. The current study aims to identify the anatomical support for aspects of reading performance that fall within these two components. Fractional anisotropy (FA) values were obtained from Diffusion Tensor images in twenty-one typical adolescents and young adults using the Tract Based Spatial Statistics (TBSS) method. We focused on the Arcuate Fasciculus (AF) and Inferior Lon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
50
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 56 publications
(60 citation statements)
references
References 83 publications
9
50
0
1
Order By: Relevance
“…Horowitz-Kraus et al (2014) found that FA values in the left ILF, as well as bilateral SLF, were significantly correlated reading comprehension. Reading comprehension was hypothesized to be related to the left ILF in the current study, because of its role in the orthographic route of reading.…”
Section: Discussionmentioning
confidence: 81%
See 3 more Smart Citations
“…Horowitz-Kraus et al (2014) found that FA values in the left ILF, as well as bilateral SLF, were significantly correlated reading comprehension. Reading comprehension was hypothesized to be related to the left ILF in the current study, because of its role in the orthographic route of reading.…”
Section: Discussionmentioning
confidence: 81%
“…Previous research has indicated a linear relation between reading comprehension and both the ILF and SLF (Feldman et al, 2012; Horowitz-Kraus et al, 2014). Horowitz-Kraus et al (2014) found that FA values in the left ILF, as well as bilateral SLF, were significantly correlated reading comprehension.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…Dunst et al (2014) found a correlation between FA in the corpus callosum and general intelligence in adult males but not in females. In older children and adolescents, higher FA values in the bilateral frontal and temporal lobes may be linked to better working memory capacity, as well as better reading ability and comprehension (Horowitz-Kraus, Wang, Plante, & Holland, 2014; Nagy, Westerberg, & Klingberg, 2004). …”
Section: Introductionmentioning
confidence: 99%